Impact of change in head and neck position on ultrasound localisation of the cricothyroid membrane: an observational study. (1st October 2018) - Dixit, A.; Ramaswamy, K. K.; Perera, S.; Sukumar, V.; Frerk, C.
Summary: The ideal position for performing surgical cricothyroidotomy is with full neck extension. Some authors have recommended marking the cricothyroid membrane before general anaesthesia, typically with the patient's head and neck in a neutral position. The primary aim of this observational study was to determine whether skin marks made over the centre of the cricothyroid membrane with the head and neck in the neutral position moved outside the boundaries of the membrane when the neck was subsequently extended. The secondary aim was to assess changes in the height of the cricothyroid membrane between the neutral and extended positions. Twenty‐two volunteers completed the study. With the head and neck in the neutral position, the distance between the upper and lower borders ('height') of the cricothyroid membrane was measured by a radiologist using ultrasound. The skin was marked over the mid‐point of the membrane. The subject then maximally extended the neck, and the measurements and marking were repeated. The skin marking over the centre point of the cricothyroid membrane moved by median (IQR [range]) 5 (4–6 [0–10]) mm when the head and neck were moved from a neutral to a fully extended position. The initial skin mark moved to lie outside the boundary of the cricothyroid membrane in 12 of 22 subjects after extending the neck. The height of the cricothyroid membrane increased by 30% with the neck extended. We recommend that marking the skin in preparation for cricothyroidotomy should be performed with the neck extended, not with the head and neck in the neutral position as previously suggested.